Estimating Tourist Externalities on Residents: A Choice Modeling Approach to the Case of Rimini - Paolo Figini; Massimiliano Castellani; Laura Vici (Fondazione Eni Enrico Mattei (FEEM), 2007)
During their holidays, tourists produce direct and indirect effects on local residents, which can either be positive or negative. In this paper we investigate how residents of Rimini, a popular Italian seaside resort hosting more than ten million national and foreign overnight stays every year, internalise such effects. We use a stated preference approach and, in particular, a discrete choice modelling technique; within this framework, we are able to test some conjectures about residents welfare, by measuring their willingness to pay for alternative scenarios regarding the use of the territory. Tourist policies and public investments in the destination affect residents welfare, and our results might suggest areas of potential synergies and trade-off, leading to important policy implications.
Keywords: Q56; L83; C25; 330; Tourism; External Effects; Discrete Choice Modelling; Tourismus; Externer Effekt; Diskrete Entscheidung; Rimini